Analisis Tegangan Pada Poros Engkol Piston Dengan Material Alumunium 6061 Menggunakan Ansys 18.1 - Muhammad Zanu Nur Arsyad; Mohamad Nanda Safitra; Dzilan Auliya Sulthon; Rachmat Nurcahyo; Trisma Jaya Saputra (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
The crankshaft is one of the main components that works in a combustion engine as a converter of the up-and-down motion of the piston into a rotary motion against the shaft used to drive chain wheel components, gears, or other components. In the research conducted, namely the analysis of the use of materials on the crankshaft using Ansys software with the aim of knowing the stress distribution, displacement, and safety factor. conclusion where the value of the radial free force of the crankshaft is 15 N, and the data that takes place on the crankshaft as follows: Based on the results of the analysis using Ansys, the maximum stress of 0.0866 N/mm2 is obtained. The displacement that occurs using Ansys analysis is 1.3461e-03mm. The safety factor that has been analyzed is 1.5 + 10.